2016
DOI: 10.1104/pp.15.01624
|View full text |Cite
|
Sign up to set email alerts
|

Combined Chlorophyll Fluorescence and Transcriptomic Analysis Identifies the P3/P4 Transition as a Key Stage in Rice Leaf Photosynthetic Development

Abstract: Leaves are derived from heterotrophic meristem tissue that, at some point, must make the transition to autotrophy via the initiation of photosynthesis. However, the timing and spatial coordination of the molecular and cellular processes underpinning this switch are poorly characterized. Here, we report on the identification of a specific stage in rice (Oryza sativa) leaf development (P3/P4 transition) when photosynthetic competence is first established. Using a combined physiological and molecular approach, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 108 publications
4
31
0
Order By: Relevance
“…In situ hybridization analyses demonstrated that OsSHR1 was expressed uniformly throughout the epidermis at the base of young leaf primordia, whereas the expression of OsSHR2 was undetectable in either shoots or roots (Kamiya et al, 2003). This difference in expression level also was seen in recent transcriptomic data sets, where OsSHR1 transcript levels were three times higher than those of OsSHR2 (van Campen et al, 2016). Notably, at the same stage that OsSHR1 transcripts accumulate uniformly in the epidermis, OsSCR1 transcripts are localized specifically in the files of small epidermal cells that will become stomatal rows (Kamiya et al, 2003).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…In situ hybridization analyses demonstrated that OsSHR1 was expressed uniformly throughout the epidermis at the base of young leaf primordia, whereas the expression of OsSHR2 was undetectable in either shoots or roots (Kamiya et al, 2003). This difference in expression level also was seen in recent transcriptomic data sets, where OsSHR1 transcript levels were three times higher than those of OsSHR2 (van Campen et al, 2016). Notably, at the same stage that OsSHR1 transcripts accumulate uniformly in the epidermis, OsSCR1 transcripts are localized specifically in the files of small epidermal cells that will become stomatal rows (Kamiya et al, 2003).…”
mentioning
confidence: 65%
“…2C). Notably, the time window of OsSHR2 expression encompasses P3, which is when files of small cells that will become stomata are first visible in the epidermis (van Campen et al, 2016). The timing of OsSHR2 transcript accumulation in leaf veins, therefore, precludes a role in procambium formation but is consistent with a subsequent role in cellular differentiation, including the specification of stomatal cell files in the overlying epidermis.…”
Section: Duplicate Shr Genes In Grassesmentioning
confidence: 99%
“…Real‐time quantitative PCR analysis was performed using the Rotor‐Gene SYBR Green PCR Kit (400) and a Corbett Rotor Gene 6000 (Qiagen) using primers (F: CCCCTTTTCCACAGATGATGTAGTA; R: GCTGTGGCCTGTGGTGAGA). Relative expression values were calculated by normalizing the take‐off value and amplification efficiency of the genes analysed relative to the Profilin (LOC_Os06g05880) housekeeping gene (van Campen et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Chloroplasts develop from proplastids under adequate light conditions, and this process involves the coordinated expression of both plastid and nuclear-encoded genes (Pogson and Albrecht 2011;Yagi and Shiina 2014). In rice, proplastid development is synchronous with leaf development, with early chloroplast development occurring at the P4 stage of leaf development (Kusumi et al 2010;van Campen et al 2016).…”
Section: Introductionmentioning
confidence: 99%